Los protagonistas de la prensa (Los primeros escritores de periódicos costarricenses. 1833-1850) - Vega Jiménez, Patricia (Revista de historia., 1993)
The purpose of this article is to analyze the main writers publishing in Costa Rican newspapers during the first half of the 19th century. This is a prior step for a discussion of the development of the press and the collective transmission of ideas by means of printed material, and of their impact of 19th century society.